Evaluation of GWAS candidate susceptibility loci for uterine leiomyoma in the multi-ethnic NIEHS uterine fibroid study - Aissani, Brahim; Zhang, Kui; Wiener, Howard (Frontiers in Genetics, 2015)
We evaluated the association of 56 candidate SNPs identified in two published genome-wide association studies (GWAS) of uterine leiomyoma (UL), or fibroids, with the risk and tumor size in the multi-ethnic uterine fibroid study (NIEHS-UFS). The selected SNPs were genotyped in 916 premenopausal women of African American (AA) and European American (EA) descents and their association with the outcomes was evaluated in race-stratified models and in meta-analysis of risk in NIEHS-UFS and discovery and replication GWAS in the Japanese population. We report moderate associations of variant rs4954368 in THSD7B (thrombospondin, type I, domain containing 7B) with tumor size in pooled analysis of AA and EA samples (P = 0.004), and at TNRC6B (trinucleotide repeat containing 6B) variants rs138039 and rs139909 in EA (P = 0.001 and P = 0.008, respectively). The most significant associations with risk in meta-analysis were observed at TNRC6B variants rs739182 (P = 3.7 x 10-10) and rs2072858 (P = 1.1 x 10-9) and were stronger than those reported in the discovery GWAS (P =2.01 x 10-8 and P = 2.58 x 10-8, respectively). The present study failed to replicate the associations reported for CCDC57 and FASN in a discovery GWAS in populations of European descent. Consistent with previous replication studies in the Right From the Start Study (RFTS) and the BioVU DNA repository, we provide independent evidence for association of TNRC6B with both risk and size of UL. The present study is the first to report a replicated association of THSD7B with UL, albeit with tumor size and not with risk.